2017
DOI: 10.1038/srep46171
|View full text |Cite
|
Sign up to set email alerts
|

Odorant cues linked to social immunity induce lateralized antenna stimulation in honey bees (Apis mellifera L.)

Abstract: Hygienic behaviour (HB) is a social immunity trait in honey bees (Apis mellifera L.) whereby workers detect, uncap and remove unhealthy brood, improving disease resistance in the colony. This is clearly economically valuable; however, the molecular mechanism behind it is not well understood. The freeze-killed brood (FKB) assay is the conventional method of HB selection, so we compared odour profiles of FKB and live brood to find candidate HB-inducing odours. Surprisingly, we found that significantly more brood… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 47 publications
0
18
1
Order By: Relevance
“…Recently, we published the paper "Odorant cues linked to social immunity induce lateralized antennal stimulation in honey bees (Apis mellifera L.)" in Scientific Reports (4). Since then, we have followed up on our electroantennography results and found that our new data are inconsistent with what we published previously.…”
Section: Introductioncontrasting
confidence: 55%
“…Recently, we published the paper "Odorant cues linked to social immunity induce lateralized antennal stimulation in honey bees (Apis mellifera L.)" in Scientific Reports (4). Since then, we have followed up on our electroantennography results and found that our new data are inconsistent with what we published previously.…”
Section: Introductioncontrasting
confidence: 55%
“…Protein was extracted by homogenizing each mite stage with ceramic beads as previously described ( 31 ). Clarified lysate was precipitated overnight with four volumes of 100% ice cold acetone, and the pellet was washed twice with ice cold 80% acetone.…”
Section: Methodsmentioning
confidence: 99%
“…For the sexual differentiation analysis, which excluded egg and protonymph stages, this was not the case, so missing values were imputed (width = 0.3, downshift = 1.5) to capture sex-specific proteins as previously described ( 36 ). Differential expression analysis across developmental stages was performed as previously described ( 31 ) except Perseus v1.5.6.0 was used, missing values were not imputed, and the ANOVA (one factor, seven levels) p values were Benjamini Hochberg-corrected at 5% FDR. For the analysis of sexually regulated genes, the female (deutonymph, adult daughter, and foundress) and male (deutonymph, adult son) samples were pooled as n = 9 and n = 6, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we compared odorant profiles of freeze-killed pupae and healthy pupae to find candidate hygienic behavior-inducing compounds 40 . Although freeze-killing is not a natural means of death, it is a relevant system because the freeze-killed brood assay 41 is the main method for determining colonies’ level of hygiene.…”
Section: Introductionmentioning
confidence: 99%
“…The queen also produces β-ocimene, which also contributes to inhibiting worker egg-laying 47 . Prior to our work in 2017 40 , β-ocimene and oleic acid had not been linked to hygienic behavior in honey bees.…”
Section: Introductionmentioning
confidence: 99%